Penerapan Konseling Behavioral Teknik Modelling Untuk Mengatasi Kecanduan Game Online Pada Anak Usia 10 Tahun - Gunawan, Didik (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
Addiction to online games is an excessive behavior to play online games that have an impact on the formation of maladaptive behavior, not in accordance with the norms prevailing in the community. Counseling behavioral modeling techniques is one of the services that are considered appropriate to overcome online game addiction problems. The purpose of this study is to determine whether counseling behavioral modeling techniques can be applied to overcome online game addiction in children aged 10 years. The type of research used by researchers is the type of single subject research, using the A-B research design (A = baseline condition, B = intervention condition). A-B shows two stages of design; A is baseline data (pretest) and B is intervention (posttest). The results showed that behavioral counseling modeling techniques were effective for reducing online game addiction in children aged 10 years.